Ambiguous order military forces in African states - Howe, Hebert M. (Boulder Lynne Rienner Publishers, 2000)
This original work examines three potential options for increasing state security in contemporary Africa: regional military groupings, private security companies, and a continent-wide, professional peacekeeping force. Howe explores these alternatives within the larger context of why African militaries have proven incapable of handling new types of insurgency; how the failed intervention in Somalia has limited Western efforts to act in subsequent crises, such as the genocide in Rwanda; and how African attempts to redefine "sovereignty" provide philosophical justification for armed intervention in the internal affairs of other states. Based on extensive travel in African war zones, his findings provide an important contribution to the growing field of African security.
Includes bibliographical references (p. ) and index.
Keywords: National security